Phases of Human Creation from the Scientific Interpretation Perspective of the Ministry of Religion of the Republic of Indonesia - Kemal Bagja; Usman, Muhamad Hafidz; Abun Nasheer, Rega; Fathurabani, Ali; Baasil Wafdulloh, Muhammad (Journal of Ulumul Qur'an and Tafsir Studies, 2024)
This article discusses the creation or origins of humans as stated in Q.S Ali-Imran: 59, Q.S. Al-Mu'minun: 12-14. This study uses a qualitative comparative study method with a literature review approach. The data source is the book "Tafsir Kemenag". Data collection techniques use search methods and data analysis techniques use content analysis. This article explains the basic stages of human creation, namely that there are several stages starting from sperm-egg cells, uterus, alaqah formation, embryo formation, bone formation, muscle formation, fetal development and metaphysical development. The question of when life on earth began to exist has been answered unequivocally by the Qur'an. According to the Qur'an, life began when the universe was created in Q.S al-Anbiya: 30.